2011
DOI: 10.1007/s12649-011-9075-5
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Residual Agroindustrial Cakes by Fungal Production of Multienzyme Complexes and Their Use in Cold Hydrolysis of Raw Starch

Abstract: In this work four agroindustrial cakes were used as raw material both for production of enzyme pools containing amylases and accessory hydrolases by solidstate fermentation (SSF) and for cold starch hydrolysis. Eight fungal strains from the genera Aspergillus and Penicillium were screened for enzyme production, and their enzyme extracts were then evaluated in the hydrolysis of raw cakes. Babassu cake was the most suitable raw material for endoamylases, exoamylases and proteases production. The highest activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 48 publications
2
22
0
1
Order By: Relevance
“…Microbiology: Understanding of metabolic mechanisms and adaptation of microbial cells for tolerance to higher concentrations of ethanol [76], as well as selection of self-floculating yeasts [52]; 4. Enzyme technology: Formulation of synergistic enzyme pools for raw starch hydrolysis [77]; production of proteolytic enzymes for the pretreatment of grains, aiming at promoting higher exposure of starch to amylases [71,78]; and use of protein engineering for the development of enzymes with improved action towards raw substrates [79]; 5. Process engineering: Some trends comprise the integration of conversion steps, e.g., simultaneous liquefaction, saccharification and fermentation [71] or simultaneous fermentation and distillation; optimization of process control, by using dynamic strategies [71,80]; very high gravity fermentation, which contributes to the reduction of capital costs and to the increase of plant throughput [81,82]; and co-product valorization, through the post-processing and fractionation of DDGS for the separation of higher value-added components and improved use as animal feed, as well as the recycle of polysaccharidic fractions to the process, aiming at the increase of the overall yield [56,83].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiology: Understanding of metabolic mechanisms and adaptation of microbial cells for tolerance to higher concentrations of ethanol [76], as well as selection of self-floculating yeasts [52]; 4. Enzyme technology: Formulation of synergistic enzyme pools for raw starch hydrolysis [77]; production of proteolytic enzymes for the pretreatment of grains, aiming at promoting higher exposure of starch to amylases [71,78]; and use of protein engineering for the development of enzymes with improved action towards raw substrates [79]; 5. Process engineering: Some trends comprise the integration of conversion steps, e.g., simultaneous liquefaction, saccharification and fermentation [71] or simultaneous fermentation and distillation; optimization of process control, by using dynamic strategies [71,80]; very high gravity fermentation, which contributes to the reduction of capital costs and to the increase of plant throughput [81,82]; and co-product valorization, through the post-processing and fractionation of DDGS for the separation of higher value-added components and improved use as animal feed, as well as the recycle of polysaccharidic fractions to the process, aiming at the increase of the overall yield [56,83].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some biomass characteristics, such as inorganic matter, carbohydrates, protein and lipid content, bulk density, elemental analysis (C, N, H, S), calorific value, particle size distribution, and porosity, alter the performance of the process where they are employed, and should be evaluated according to the purpose of the study [59]. It was demonstrated for example that C/N ratios higher than 10 are advantageous for enzyme production, (e.g., protease, amylase, cellulose, and xylanase) in SSF processes [60]. SSF process has the possibility of using agro-industrial residues that are cheap and readily available in several countries including Brazil, India, and the United States [13,34].…”
Section: Use Of Solid Waste To Obtain Biocatalystsmentioning
confidence: 99%
“…Another source of variation is the method used for the quantification of enzyme activity, as well as the definition of enzyme activity. The production of amylases by eight fungal strains using four different agroindustrial by-products was recently reported, and very distinct results were observed in each case [61]. Also, Castro and Ribeiro [62] reviewed methods to determine activities of endoamylases, exoamylases, and debranching amylases, reporting at least ten different literature-cited methods for the quantification of these enzymes.…”
Section: Amylasesmentioning
confidence: 99%